2020
DOI: 10.1172/jci.insight.135597
|View full text |Cite
|
Sign up to set email alerts
|

Commensal bacteria stimulate antitumor responses via T cell cross-reactivity

Abstract: and Eisai. TAC has served as an advisor for Bristol Myers Squibb, Illumina, Eisai, and An2H. Under a licensing agreement between NexImmune and the Johns Hopkins University, JPS is entitled to shares of royalty received by the university on sales of artificial antigen-presenting cell products described in this article. He also owns NexImmune stock, which is subject to certain restrictions under university policy. JPS is a member of the company's Scientific Advisory Board. The terms of this arrangement are being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 44 publications
0
103
0
Order By: Relevance
“…In pancreatic cancer, a unique microbiome composition has been observed in patients with longest survival after surgery ( Riquelme et al., 2019 ). Cross-reactive T cells recognizing both tumor antigens and microbial antigens have also been shown to control tumor growth in mouse models ( Bessell et al., 2020 ; Fluckiger et al., 2020 ). In addition, EBV and flu have recently been shown to induce anti-tumor immunity against shared TAAs ( Choi et al., 2020 ; Newman et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic cancer, a unique microbiome composition has been observed in patients with longest survival after surgery ( Riquelme et al., 2019 ). Cross-reactive T cells recognizing both tumor antigens and microbial antigens have also been shown to control tumor growth in mouse models ( Bessell et al., 2020 ; Fluckiger et al., 2020 ). In addition, EBV and flu have recently been shown to induce anti-tumor immunity against shared TAAs ( Choi et al., 2020 ; Newman et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, tumors expressing the TAA also grew faster in mice lacking Bifidobacterium breve bacterium. 79 Of note, memory immune reactivity against B. longum also correlated with robust CD8 + T cell responses and better prognosis in HBV-related hepatocellular carcinoma patients. 76 The first bacterial species known to harbor "zwitterionic" peptides capable of engaging CD4+ T cell receptors was Bacteroides fragilis.…”
Section: Identification Of Key Bacteria Boosting the Antitumoral Effimentioning
confidence: 95%
“… 24 A recent study unveiled that the SIY antigen (TAA) of B1610 displayed antigen mimicry with an epitope belonging to Bifidobacterium breve, accounting for the T cell–mediated antitumor responses achieved by oral supplementation with this probiotic. 79 Accordingly, T cells targeting the microbial antigen recognized melanoma tumor cells expressing the SIY tumor-associated antigen. Conversely, tumors expressing the TAA also grew faster in mice lacking Bifidobacterium breve bacterium.…”
Section: Identification Of Key Bacteria Boosting the Antitumoral Effimentioning
confidence: 99%
“… Oral gavage of susceptible (NZW × BXSB)F 1 mice with R. intestinalis induces anti-human β2GPI autoantibodies and lethal thromboses 3 Cancer: Multiple transplantable mouse cancers TSLARFANI contained in the TMP1 protein expressed by an enterococcal phage GSLARFRNI contained in PSMB4 protein Mouse K b Colonization with Enterococcus hirae or Escherichia coli expressing the TMP1 epitope improves control of MCA205 fibrosarcomas 4 Cancer: Lung adenocarcinoma + kidney cancer KLAKFASVV contained in the TMP1 expressed by an enterococcal phage KLQKFASTV contained in GPD1-L protein HLA-A*0201 Cross-reactive T cells found in non-small cell lung cancer patients. Presence of TMP1 associated to good prognosis in patients treated with PD-1 blockade 4 Cancer: melanoma SVYRYYGL expressed by Bifidobacterium breve SIYRYYGL artificially introduced into B16 melanoma cells Mouse K b Colonization with B. breve allows for melanoma control 5 Multiple melanoma antigen-homologous peptides identified by bioinformatics within the human intestinal microbiota EAAGIGILTV present in the MART-1 protein and TLNDECWPA present in MELOE1 HLA-A*0201 In vitro evidence of cross-reactive T cells with defined TCR sequences 4 Inflammatory cardiomyopathy FLILMAALTATFASAQ contained in β-galactosidase from Bacteroides thetaiotaomicron and B. faecis SLKLMATLFSSYATAD from human myosin heavy chain 6 (MYH6) HLA-DQB1* Bacteroides -specific CD4 + T cell and B cell responses found in human myocarditis patients. B. thetaiotaomicron monocolonization expressing the β-galactosidase epitope favors myocarditis development in mice expressing a MYH6- specific T cell receptor on more than 95% of their CD4 + T cells.…”
mentioning
confidence: 99%
“…In a pioneering report, Bessel et al demonstrated that a peptide expressed by Bifidobacterium breve can cross-react with a tumor antigen that was artificially induced into B16 melanoma cells. 5 A more recent study from our laboratories demonstrated that a peptide (within the tape measure protein TMP1) encoded by the genome of a 39.2-kb prophage from the Siphoviridae bacteriophage family, which lysogenizes Enterococci , can cross-react with a peptide contained in a natural protein (PSMB4, which is an oncogenic proteasome subunit) expressed by mouse fibrosarcomas and lung cancers. 4 The relevance of this cross-reactivity for tumor control was demonstrated by several lines of evidence, including the observations that (1) only Enterococci harboring the bacteriophage-encoded TMP1 epitope favor immune control of tumors; (2) point mutations of the bacteriophage-encoded TMP1 epitope abolished such an immune control; (3) transfer of the TMP1 epitope into Escherichia coli conferred antitumor immunity-inducing properties to this usually inert bacterium if it was orally administered to mice; (4) mutation of the PSMB4 epitope in tumor cells rendered them resistant to TMP1-encoding bacteriophage-elicited immunosurveillance.…”
mentioning
confidence: 99%